Function conservation and disparities of zebrafish and human LGP2 genes in fish and mammalian cells responsive to poly(I:C) - Gong, Xiu-Ying; Qu, Zi-Ling; Li, Yi-Lin; Sun, Hao-Yu; Zhao, Xiang; Dan, Cheng; Gui, Jian-Fang; Zhang, Yi-Bing (Frontiers in Immunology, 2022)
Retinoic acid inducible gene-I (RIG-I)-like receptors (RLRs) are viral RNA sensors that regulate host interferon (IFN)-mediated antiviral signaling. LGP2 (laboratory genetics and physiology 2) lacks the N-terminal caspase activation and recruitment domains (CARDs) responsible for signaling transduction in the other two RLR proteins, RIG-I and melanoma differentiation associated gene-5 (MDA5). How LGP2 regulates IFN signaling is controversial, and inconsistent results have often been obtained in overexpression assays when performed in fish cells and mammalian cells. Here we report that the differential sensitivity of fish cells and mammalian cells to poly(I:C) transfection conceals the function conservation of zebrafish and human LGP2. In fish cells, overexpression of zebrafish or human LGP2 initially activates IFN signaling in a dose-dependent manner, followed by inhibition at a critical threshold of LGP2 expression. A similar trend exists for LGP2-dependent IFN induction in response to stimulation by low and high concentrations of poly(I:C). In contrast, overexpression of zebrafish or human LGP2 alone in mammalian cells does not activate IFN signaling, but co-stimulation with very low or very high concentrations of poly(I:C) shows LGP2-dependent enhancement or inhibition of IFN signaling, respectively. Titration assays show that LGP2 promotes MDA5 signaling in mammalian cells mainly under low concentration of poly(I:C) and inhibits RIG-I/MDA5 signaling mainly under high concentration of poly(I:C). Our results suggest that fish and human LGP2s switch regulatory roles from a positive one to a negative one in increasing concentrations of poly(I:C)-triggered IFN response.